Prognostic indicators in pediatric clinically isolated syndrome. Issue 5 (May 2017) - Iaffaldano, Pietro; Simone, Marta; Lucisano, Giuseppe; Ghezzi, Angelo; Coniglio, Gabriella; Brescia Morra, Vincenzo; Salemi, Giuseppe; Patti, Francesco; Lugaresi, Alessandra; Izquierdo, Guillermo; Bergamaschi, Roberto; Cabrera‐Gomez, Jose Antonio; et al.
Abstract : Objective: To assess prognostic factors for a second clinical attack and a first disability‐worsening event in pediatric clinically isolated syndrome (pCIS) suggestive of multiple sclerosis (MS) patients. Methods: A cohort of 770 pCIS patients was followed up for at least 10 years. Cox proportional hazard models and Recursive Partitioning and Amalgamation (RECPAM) tree‐regression were used to analyze data. Results: In pCIS, female sex and a multifocal onset were risk factors for a second clinical attack (hazard ratio [HR], 95% confidence interval [CI] = 1.28, 1.06–1.55; 1.42, 1.10–1.84, respectively), whereas disease‐modifying drug (DMD) exposure reduced this risk (HR, 95% CI = 0.75, 0.60–0.95). After pediatric onset MS (POMS) diagnosis, age at onset younger than 15 years and DMD exposure decreased the risk of a first Expanded Disability Status Scale (EDSS)‐worsening event (HR, 95% CI = 0.59, 0.42–0.83; 0.75, 0.71–0.80, respectively), whereas the occurrence of relapse increased this risk (HR, 95% CI = 5.08, 3.46–7.46). An exploratory RECPAM analysis highlighted a significantly higher incidence of a first EDSS‐worsening event in patients with multifocal or isolated spinal cord or optic neuritis involvement at onset in comparison to those with an isolated supratentorial or brainstem syndrome. A Cox regression model including RECPAM classes confirmed DMD exposure as the most protective factor against EDSS‐worsening events and relapses as the most important risk factor for attaining EDSS worsening. Interpretation: This work represents a step forward in identifying predictors of unfavorable course in pCIS and POMS and supports a protective effect of early DMD treatment in preventing MS development and disability accumulation in this population. Ann Neurol 2017;81:729–739